Preliminary Investigation on Enhanced Hydrogen Generation via Carbon Nanodots–Sulfonated Polyoctahedral Silsesquioxane Layer Modified Anode in Water Electrolysis (Journal of Applied Membrane Science & Technology, 2025)
This study investigated the preliminary electrochemical performance of carbon anodes coated with a composite of Carbon Nanodots (CND) and Sulfonated Polyoctahedral Silsesquioxane (SPOSS) for water electrolysis. The coatings were applied in varying ratios of CND to SPOSS (1:0, 1:1, 0:1) and at different layer thicknesses (3 and 5 layers) simulating membrane-like interfaces for enhanced electrode–electrolyte interaction. Electrochemical performance was evaluated through hydrogen production rates in a 2 wt% NaOH electrolyte. Scanning Electron Microscopy (SEM) was used to confirm the uniformity and integrity of the coatings, while UV-Vis Spectroscopy was employed to assess any potential leaching of coating materials into the electrolyte. Results indicated that electrodes coated with CND:SPOSS (1:1) modification with three coating layers improved both catalytic activities, achieving the highest hydrogen production rate of 0.51 cm³/s. Excessive coating thickness, particularly at five layers, led to aggregation observed in the SEM images, which resulted in a reduced hydrogen production rate and overall performance. The 3-layer CND:SPOSS (1:1) coating is optimal for hydrogen production performance due to its uniform, crack-free structure and enhanced electrochemical activity, while the 3-layer CND:SPOSS (0:1) coating is best for minimizing leaching, as it shows the least absorbance increase. These preliminary findings highlight the potential of nanocarbon-based surface modification as a membrane-inspired strategy to enhance hydrogen production efficiency in alkaline water electrolysis systems.
Keywords: Carbon Nanodots (CND), Sulfonated Polyoctahedral Silsesquioxane (SPOSS), Anode Layers, Alkaline Water Electrolysis, Hydrogen Generation